RENEWABLE ENERGIES AND ECONOMIC DEVELOPMENT: EVIDENCES OF STUDY IN PANEL - Lameira, Valdir; Alcântara, Fabiana; Chiappori, Dino; Pereira, Roberto (Brazilian Journal of Operations & Production Management, 2016)
The concerns with sustainability in environmental and social realm led to an expressive increase in generation of energy of renewable sources in last years. This paper addresses an investigation on possible associations between the increase of renewable energies generation and the economic and financial performance indicators of countries. The multiple linear regressions method is applied to a data panel of the period from 2005 to 2008, in 54 countries. The outcomes point to an association between higher generation of renewable energies and lower GDP growths, higher per capita income and higher investments in gross fixed capital formation, besides other interesting associations.